Determination of Variability, Heritability, Genetic Advance and Their Interrelationships in Rabi Sorghum (Sorghum bicolor L. Moench) for Various Yield and Yield Contributing Traits under Drought Conditions - Kesoju Ravali; J. E. Jahagirdar (Current Topics in Agricultural Sciences Vol. 8, 2022)
For effective selection of a crop species studying the genetic variability parameters plays a key role. Primary requirement of any breeding program for the crop improvement is the presence of desirable variation and the amount of that variation which is heritable. As a result, any breeding effort for crop development is heavily reliant on genetic variability, heritability, and genetic progress. During rabi 2019, the genetic variability study for yield and yield contributing variables in 37 genotypes of rabi sorghum with three checks, M 35-1, Phule Suchitra, and CSV-22-R, was carried out at Sorghum Research Station, V.N.M.K.V., Parbhani. The treatments were reviewed and data for 11 traits were recorded using a randomised block design with three replications, with the goal of estimating the genetic variability for quantitative traits. The presence of highly significant differences among genotypes was discovered, demonstrating a great level of variability in all 11 features tested. When phenotypic coefficients of variation are compared to genotypic coefficients of variation, greater estimates of phenotypic coefficients of variation are found, and these estimates are of smaller magnitude. VJV 107, VJV 106, PEC 30, RSV 1921, RSV 1945, and RSV 1984 were regarded the superior genotypes among the forty genotypes studied because they performed better. The present study was undertaken with objective to estimate the genetic variability for the quantitative traits.